Knowledge, Skills & Competencies: A Capability Approach With Strategic Implications - Chao, Emmanuel (Journal of Knowledge Management Practice, 2011)
This paper aims at reconsidering knowledge, skills and competencies from a capability perspective while addressing firms’ strategic response. This is a one of recent attempts in adressing capabilities from a two dimensional form, and identifying the nature of capabilities (knowledge, skills and competencies) with respect to this classification and aligning them with the firms’ strategic growth objectives. This paper has identified four forms of capabilities based on this classification. These include; Localized capabilities, Blocked (sticky) capabilities, Narrow capabilities, and Multiplex Capabilities. Though localized capabilities are hard for competitors to imitate, they add less value to firms’ growth options. Multiplex capabilities have a possibility to provide firms with multiple growth options but this come at the expense of more risks from competitor’s attempts to imitate, which lead to their value erosion. Responding to the risky nature of multiplex capabilities, firms need to insulate themselves by ensuring their value generation is contingent on other assets inside the firm.
Keywords: knowledge management; Capabilities; Knowledge; Skills; Competencies; Transferability; Generalizability